Antecedents and Outcome of Union Commitment. [article]. - Acayan, A.
There is an apparent decline in union membership across industries in the Philippines. The study tried to understand this phenomenon by determining factors that lead to union commitment using a framework derived from existing models of union commitment and participation. Survey data were gathered from 194 union members belonging to academic and financial institutions, and pharmaceutical industries. Path analysis was used to analyze the data. The resulting model verified that organization commitment, perceived union instrumentality, pro-union attitude, and union socialization are predictors of union commitment. Furthermore, union commitment leads to union participation. Findings suggest that unions may enhance member commitment and participation in union activities by utilizing informal socialization practices.
Keywords: Union; Organization; Commitment; Participation; Outcome